A “Killing Fully Acceptable to God”: Sepúlveda and Erasmus on the War against the Turks - Carman, Glen (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2024)
Sultan Suleiman’s siege of Vienna in 1529 prompted a new round of treatises from humanists proposing ways to confront the Ottoman threat, including from Erasmus of Rotterdam and Juan Ginés de Sepúlveda, who approached the question from almost opposite positions. This article examines how the antimilitarist Erasmus responded to the imperialistic aspirations of such calls to arms as the exhortation written by Sepúlveda. Whereas Sepúlveda sees war with the Ottomans as an existential battle of civilizations, Erasmus looks inward for the causes of the conflict and the path to victory, both of which he connects to the urgent need for reform from within. The metaphorically violent edge of Erasmus’s appeal to battle an “interior Turk” conjures up cultural as well as religious hierarchies, but his dual understanding of the threat to Christianity as coming from both within and without distinguishes it from much of the chauvinism fomented by war.